Design and research of life-saving cotton-blended miners' clothing. Issue 3 (3rd July 2022) - Xiangfang, Ren; Lei, Shen; Xiying, Zhang; Han, Chen; Yan, Huang; Peng, Jin
Abstract : Miners face a series of potential safety hazards in underground work, among which the life-saving function of miners' clothing is particularly important. This article investigates the causes of current mine accidents and the impact of the mine environment, analyses the design and research status of miners' uniforms from the perspective of the market and academia, and emphasizes and puts forward the idea of optimizing the design of miners' uniforms through the characteristics of miners' underground operation and the requirements for their protective performance. Based on the 2F (fashion, function) design model, the basic principles of miners' clothing design are summarized. The design of miners' clothing is studied from three design factors: positioning element, structural design and protective fabric. The purpose is to improve miners' clothing for comfort, positioning, life-saving, hygienic, antimicrobial, etc., shorten search and rescue times, and improve rescue times in mining accidents, to increase the survival rate.